Gendered Challenges in Nepal’s TVET Sector: A Narrative Inquiry of Women Instructors - Sharma, Dipika (Journal of Technical and Vocational Education and Training, 2026)
In spite of increasing research on gender and education in Nepal, there is a meager literature on how women instructors in the technical and vocational education and training (TVET) sector narrate their lived professional experiences. This research explores the lived experiences of four women instructors working in the TVET institutions in Nepal. The study focuses on how these four instructors share the personal account and make sense of their professional journeys, including the challenges they face, the strategies they use to overcome barriers, and the opportunities they create within their institutions. Using a narrative inquiry as the research method and working within an interpretive research paradigm, the study draws on in-depth interviews and field notes from four women instructors. The feminist theory and cultural capital theory are applied to explain how gender roles and cultural experiences influence teaching practices and leadership development. The findings reveal that each woman’s story is shaped by her unique socio-cultural background, psychological resilience and professional growth. Despite facing male dominance, gender bias, and limited institutional support, the instructors show strong leadership, adaptability and commitment to quality education. Their experiences highlight the importance of participatory leadership, self-reflection, content expertise and culturally responsive teaching. The study concludes that women instructors play a vital role in shaping inclusive and productive learning environments and their voices must be recognized for the betterment of TVET in Nepal.